Reporter na wojnie. Na przykładzie pracy korespondentów „Polityki” i „Tygodnika Powszechnego” z Ukrainy po 24 lutego 2022 roku - Borkowski, Igor (Przegląd Wschodnioeuropejski, 2025)
Igor Borkowski analyses techniques and dilemmas used in reporting on the military conflict following Russia’s attack on Ukraine (February 24, 2022), on the example of reportage materials published in the Polish weekly “Polityka” and “Tygodnik Powszechny”. The text establishes what are currently the main problems and dilemmas in the field of war journalism and the work of a war correspondent. It is indicated to what extent these problems are new compared to the tradition of war reportage formed in the 20tt century. Techniques for reporting events on the war front, describing the situation of soldiers and civilians, and forming the image of a professional journalist working in a country at ware are discussed.